Avoiding a Full Criminal Trial : Fair Trial Rights, Diversions and Shortcuts in Dutch and International Criminal Proceedings /: Fair Trial Rights, Diversions and Shortcuts in Dutch and International Criminal Proceedings. (2016) - Vriend, Koen
No abstract available